Assimilation of microbial and plant carbon by active prokaryotic and fungal populations in glacial forefields. (July 2016) - Rime, Thomas; Hartmann, Martin; Stierli, Beat; Anesio, Alexandre M.; Frey, Beat
Abstract: Microbial communities and soil carbon (C) have been shown to vary in response to increasing vegetation cover during soil development after deglaciation. However, little is known about the ability of microorganisms to utilize various C sources in glacier forefield soils. We supplied ecologically relevant 13 C-labeled C sources ( Chlorella, Penicillium and Festuca ) to three distinct environments (supraglacial sediments, barren soils and vegetated soils) of the Damma glacier area to monitor 13 CO2 production. We identified prokaryotic and fungal populations able to utilize these sources by using DNA-stable isotope probing coupled with Illumina MiSeq sequencing of ribosomal markers. A high initial 13 CO2 pulse indicated that 13 C-labeled microbial and plant material were consumed. The 13 C-enriched DNA results indicated that betaproteobacterial taxa affiliated to the families Oxalobacteraceae and Comamonadaceae were important players in C utilization from different sources and present in all environments. In contrast, different fungal taxa played different roles in C degradation depending on the soil environment. Overall, our findings reveal that C utilization is driven by similar prokaryotic populations along a glacier forefield, while the distribution of active fungal populations are more influenced by environmental factors. Highlights: C utilization in successive stages of soil development formed after glacier retreat. DNA-SIP coupled with Illumina MiSeq sequencing to characterize microbial C utilizers. Prokaryotic C utilizers are copiotroph and similar among stages of soil development. Fungal C utilizers are specialist and differ among stages of soil development.